Fifth Harvard University Forum Islamic Finance: Dynamics and Development (April 6-7, 2002 • Harvard University, Cambridge, Massachusetts) (American Journal of Islam and Society, 2002)
Each year, the Harvard Islamic Finance Information Program (HIFIP) of the Center for Middle Eastern Studies organizes this forum. This year's forum had an international flavor, thanks to participants from Malaysia, South Africa, the Middle East, and Europe. Participants were mainly finance industry representatives from the Islamic Development Bank, the Kuwait Finance House, HSBC Amanah Finance, the Dow Jones Islamic Index, Bank Indonesia, Freddie Mac, and others. In addition, several experts in Islamic economics and finance, such as Monzer Kahf, M. Nejatullah Siddiqi, Nizam Yaquby, and Frank E. Vogel participated. Many other participants sought to educate themselves about the principles of Islamic finance and the availability of lslamically approved financial products. Overall, the forum was more of an opportunity for those interested in Islamic finance to meet each other, network, and present some of their latest lslamically approved financial instruments and contracts. The forum featured a few research papers and many case studies. Most presentations and panel discussions focused on current and past experiences in the Islamic finance industry, challenges facing the development of new financial instruments, effective marketing and delivery of products to end-users, and areas where applying jjtihad is most needed and promising. Participants also discussed the need to develop relevant financial institutions to strengthen the stability and perfonnance of Islamic financial service providers ( e.g., managing liquidity and risk). Thomas Mullins, HIFIP's executive director, welcomed the guests. He stressed the Islamic finance industry's important role in creating a dialogue between I slam and the West - a role made especially relevant after September 11. Forum chairperson Samuel Hayes, Jacob Schiff Professor Emeritus at Harvard Business School, used his opening remarks to commend the industry on its many accomplishments during the past decade and outlined areas for improvement. In his introduction, Saif Shah Mohammed, president of the Harvard Islamic Society, suggested that the industry should prer vide relevant services to students, such as Shari'ah-compliant educational loans and young professional programs. Ahmad Mohamed Ali, president of the Islamic Development Bank (IDB), delivered the keynote address: "The Emerging Islamic Financial Architecture: The Way Ahead." He discussed the infrastructure required to strengthen the Islamic financial industry, which is in a process of evolution. Some recent major initiatives include the Accounting and Auditing Organization for Islamic Financial Institutions, the Islamic Financial Services Organization, an international Islamic financial market with a liquidity management center, and an Islamic rating agency. Currently, there are ...